체재형주말농장의 개발 방향에 관한 연구 : 전문가 설문조사를 중심으로 - 최정민 (한국농촌경제연구원, 2011)
The purpose of this study is to act as a preliminary inquiry into the development of a Korean Garden Community (K-GC) model as an element of multi-habitation community. The proposed model is based on data collected from thirty-four experts’ survey and case studies in both Korea and foreign countries. The main findings are: 1) eclectic model that will be resulted in urban-rural co-development by bridging such values as social welfare of Germany and regional economic development of Japan; 2) Main developers are suggested to be municipal governments or Korea Rural Community Corporation whereas local community organizations and local farm corporations should be a primary operating body; 3) Enacting a special regulation is to be needed to promote and stabilize the K-GC; and 4) Two different types of K-GC are needed to meet the geo-political and economic needs of each community which are called as Suburb and Countryside type of K-GC. The suburb-type of K-GC focuses on social welfare in a scale developed by public sectors, while countryside-types of K-GC emphasize regional revitalization in a medium-size complex led by citizens and groups.
Keywords: 체재형주말농장; 한국형 커뮤니티가든; 멀티해비; Kleingarten; K-GC; Korean Garden Community; multi-habitation